EXICO-SEMANTIC PROPERTIES OF ERGONIMS (Scientific journal of the Fergana State University, 2023)
This article discusses the community of people who are organized in terms of activities, as well as ergonomics, which are the famous name of institutions, organizations and enterprises. The term ergonim is derived from the Greek words ἔrgón - "work, activity, creation" and ōmona - "name", and its introduction into science, the attitude of scientists to these proper nouns has been controversial. In Uzbek linguistics, almost no attention is paid to natural and artificial nominations, this aspect of the naming process. Ergonomics, in addition to universal onomastic features, have unique features that allow it to be divided into separate groups. The ergonomic system depends in many ways on government regulation. The lexical-semantic method is the most effective in the formation of new ergonims. When using this method, familiar words and phrases are used in their meaning. Modern ergonomics are experiencing a “nominal explosion” state.